196k views
25 votes
There will be more questions just like this...

There will be more questions just like this...-example-1

2 Answers

7 votes

Answer:

Explanation:

Im not positive but,

2x - y = 1

2(-1) - ? = 1

Change it around

2(-1)= -2

-2 + 1= -1

Then (it bugged out)

Switch it back

(2×(-1))-1=

-3

-3 = y its that or -1

I dont know if i did this right I'm using my class notes

User Tonyc
by
6.6k points
4 votes

Answer:


2x - y = 1 \\ 2( - 1) - y = 1 \\ - 2 - y = 1 \\ y = - 3

User Rechlay
by
6.2k points